Efeito de diferentes tratamentos de superfície na resistência à flexão biaxial e resistência de união entre cimento resinoso e uma cerâmica Y-TZP - Pozzobon, Joao Luiz (2016)
This study evaluated the effect of different surface treatments on the biaxial flexure strength and reliability of a ceramic Y-TZP by using Weibull analysis. In addition, the influence of these methods on the bond strength of a resin cement and ceramic Y-TZP were studied. The surface treatments analyzed were the following: air-borne particle abrasion with silica-coated aluminum oxide particles for 10 s with 10 mm distance (TBS); application of a ceramic overglaze on the surface and etching with 10% hydrofluoric acid gel (HF) for 1 min (GLZ1), 5 min (GLZ5), 10 min (GLZ10), and 15 min (GLZ15); and deposition of 5 nm thick SiO2 nanofilm by physical vapor deposition (PVD) (SNF). This last treatment was performed only to study the biaxial flexural strength. Regarding the biaxial flexural strength and reliability of the material, 210 discs (15mm × 1.2mm) of Y-TZP were made following the ISO 6872-1999 and then sintered according to the manufacturer`s instructions. The discs (n=30) were divided according to the different surface treatments applied (6 groups), apart from the control group which did not receive any treatment. Using the flexural strength data, a Weibull statistical analysis was performed to describe the reliability of the ceramic material. To evaluate the bond strength, 75 Y-TZP (In-Ceram YZ, Vita) blocks (5×5×4 mm) were assigned into five groups (n=15) according to the different surface treatments. Specimens of composite resin (diameter=3.25mm; height=3mm) were cemented to the Y-TZP blocks using resin cement (Relyx ARC). All the specimens were subjected to aging (10,000 thermal cycles and storage for 90 days), tested in shear, analyzed under a stereomicroscope and under a scanning electron microscope (SEM), and measured by phase transformation analysis (XRD). In relation to the biaxial flexure, the TBS group statistically presented the highest strength values, and the groups with glaze application followed by etching with hydrofluoric acid (GLZx) showed the lowest values, independent of the HF treatment time. However, no surface treatment negatively influenced the reliability of the material when compared with the control group with no surface treatment, according to the Weibull analysis results. With respect to adhesion, the TBS groups showed the highest bond strength values. It may be concluded that treatment with blasting (TBS group) confers the best bond strength to ceramics out of all the tested methods, without negatively influencing the strength of the material.